Developing a quality criteria framework for patient decision aids: online international Delphi consensus process. Issue 7565 (14th August 2006) - Elwyn, Glyn; O'Connor, Annette; Stacey, Dawn; Volk, Robert; Edwards, Adrian; Coulter, Angela; Thomson, Richard; Barratt, Alexandra; Barry, Michael; Bernstein, Steven; Butow, Phyllis; Clarke, Aileen; et al.
Abstract: Objective To develop a set of quality criteria for patient decision support technologies (decision aids). Design and setting Two stage web based Delphi process using online rating process to enable international collaboration. Participants Individuals from four stakeholder groups (researchers, practitioners, patients, policy makers) representing 14 countries reviewed evidence summaries and rated the importance of 80 criteria in 12 quality domains ona1to9 scale. Second round participants received feedback from the first round and repeated their assessment of the 80 criteria plus three new ones. Main outcome measure Aggregate ratings for each criterion calculated using medians weighted to compensate for different numbers in stakeholder groups; criteria rated between 7 and 9 were retained. Results 212 nominated people were invited to participate. Of those invited, 122 participated in the first round (77 researchers, 21 patients, 10 practitioners, 14 policy makers); 104/122 (85%) participated in the second round. 74 of 83 criteria were retained in the following domains: systematic development process (9/9 criteria); providing information about options (13/13); presenting probabilities (11/13); clarifying and expressing values (3/3); using patient stories (2/5); guiding/coaching (3/5); disclosing conflicts of interest (5/5); providing internet access (6/6); balanced presentation of options (3/3); using plain language (4/6); basing information on up to date evidence (7/7); and establishing effectiveness (8/8). Conclusions Criteria were given the highest ratings where evidence existed, and these were retained. Gaps in research were highlighted. Developers, users, and purchasers of patient decision aids now have a checklist for appraising quality. An instrument for measuring quality of decision aids is being developed.